Polyimide and polyimide film
By introducing repeating units derived from specific diacid anhydrides and aromatic diamines into the polyimide, optimizing their structure and molar ratio, the problems of insufficient dielectricity, mechanical strength and heat resistance of existing polyimides in flexible printed circuit board insulation materials are solved, and better performance indicators are achieved.
Patent Information
- Application Number
- CN202410378160.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-03-29
- Publication Date
- 2025-03-18
AI Technical Summary
When used as insulating materials for flexible printed circuit boards, existing polyimides have problems such as poor dielectric properties, insufficient mechanical strength, excessive water absorption and insufficient heat resistance.
Using a polyimide derived from a combination of a specific diacid anhydride and an aromatic diamine, which comprises repeating units derived from diacid anhydride and repeating units derived from diamine, the dielectricity, mechanical properties and heat resistance of the polyimide are optimized by a specific molar ratio and structural design.
It realizes excellent dielectric properties, excellent mechanical strength, low water absorption and good heat resistance of polyimide, and is suitable as an insulating material for flexible printed circuit boards.
Smart Images

Figure CN119638990A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyimide, more particularly, to a polyimide comprising repeating units derived from a specific diamine combination and also to a polyimide film formed from the polyimide. Background Art
[0002] In recent years, with the booming development of wearable electronic products, the demand for flexible printed circuit boards has been increasing day by day. In order to meet the requirements of high-frequency and high-speed transmission, the insulating materials used to prepare flexible printed circuit boards must have low dielectric constant (Dk), low dissipation factor (Df), and excellent dimensional stability. If the dimensional stability of the insulating material is not good, the printed circuit board will warp due to high temperature during the packaging process, resulting in circuit peeling or cracking of the printed circuit board.
[0003] It is known that polyimide can be used as an insulating material for preparing flexible printed circuit boards. However, existing polyimide has technical problems such as poor dielectric properties, insufficient mechanical strength, and excessive water absorption, and further improvements are still needed. Summary of the invention
[0004] In view of this, the present invention provides a polyimide derived from a combination of a dianhydride and a specific diamine, which has excellent dielectric properties and excellent mechanical strength, low water absorption and good heat resistance, and is suitable as an insulating material for a flexible printed circuit board.
[0005] Therefore, an object of the present invention is to provide a polyimide comprising a repeating unit derived from a dianhydride and a first repeating unit and a second repeating unit derived from a diamine.
[0006] The first repeating unit is a repeating unit having the following formula (A):
[0007] [Formula (A)]
[0008]
[0009] In formula (A), R 1 and R 2 Each is independent R 3 and R 4 Each is independent or H, wherein m and n are each independently an integer from 1 to 16, * represents a bonding position, and The carbon-bonded position in the formula (A) is bonded to the aliphatic ring; and
[0010] The second repeating unit is a repeating unit derived from an aromatic diamine, a repeating unit having the following structure (B), or a combination thereof:
[0011] [Formula (B)]
[0012]
[0013] In formula (B), * represents a bonding position; and
[0014] The repeating unit derived from the aromatic diamine comprises a structural unit having the following formula (C): [Formula (C)]
[0015]
[0016] In formula (C), R 5 and R 6 Each is independent Covalent single bond, or where * indicates the bond position, and The bonding position to carbon in the formula (C) is bonded to the benzene ring.
[0017] In some embodiments of the present invention, the second repeating unit comprises the repeating unit derived from an aromatic diamine.
[0018] In some embodiments of the present invention, the molar ratio of the first repeating unit to the second repeating unit is 1:20 to 1:4.
[0019] In some embodiments of the present invention, the second repeating unit is a repeating unit having a structure of formula (B), and the molar ratio of the first repeating unit to the second repeating unit is 1:20 to 1:4.
[0020] In some embodiments of the present invention, the repeating unit derived from an aromatic diamine comprises at least one structural unit selected from the following group:
[0021] Where * indicates the bonding position.
[0022] In some embodiments of the present invention, the repeating unit derived from an aromatic diamine is at least one selected from the following group: and Where * indicates the bonding position.
[0023] In some embodiments of the present invention, the first repeating unit is a repeating unit having the following structure (A1):
[0024] [Formula (A1)]
[0025]
[0026] In formula (A1), m1, m2, n1, and n2 are each independently an integer from 0 to 14, and * represents a bonding position.
[0027] In some embodiments of the present invention, the first repeating unit is at least one selected from the following group:
[0028] Where * indicates the bonding position.
[0029] In some embodiments of the present invention, the repeating unit derived from a dianhydride is at least one selected from the following group: and Where * indicates the bonding position.
[0030] In some embodiments of the present invention, the repeating unit derived from the dianhydride is
[0031] combination.
[0032] Another object of the present invention is to provide a polyimide film, which is made from the polyimide as described above.
[0033] In order to make the above-mentioned objectives, technical features and advantages of the present invention more obvious and easy to understand, some specific implementation schemes are described in detail below. DETAILED DESCRIPTION
[0034] Some specific embodiments according to the present invention will be described in detail below; however, without departing from the spirit of the present invention, the present invention can also be practiced in a variety of different forms of solutions, and the protection scope of the present invention should not be limited to the specific embodiments.
[0035] Unless otherwise stated, the terms “a”, “an”, “the” and similar terms used in the specification and claims should be understood to include both the singular and the plural.
[0036] Unless otherwise specified, the terms “first”, “second” and the like used in the specification and the claims are merely used to distinguish described elements or components and have no special meanings by themselves and are not intended to refer to a sequential order.
[0037] 1. Polyimide
[0038] Generally speaking, the synthesis method of polyimide may include a two-stage condensation method and a one-stage condensation method. The two-stage condensation method generally forms polyamic acid (PAA) by condensation polymerization of dianhydride and diamine, and then heats and dehydrates the polyamic acid to form polyimide. The one-stage condensation method generally forms polyimide by reacting dianhydride and diisocyanate at high temperature. Regardless of the two-stage condensation method or the one-stage condensation method, the existing polyimide does not have excellent dielectric properties, excellent mechanical strength, excellent dimensional stability, low water absorption and good heat resistance. The present invention provides a polyimide derived from a combination of dianhydride and a specific diamine. The polyimide of the present invention has excellent dielectric properties and excellent mechanical strength, low water absorption and good heat resistance, and is suitable as an insulating material for a flexible printed circuit board. The polyimide of the present invention may include a repeating unit derived from a dianhydride and a first repeating unit and a second repeating unit derived from a diamine. In some embodiments of the present invention, the polyimide of the present invention consists essentially of a repeating unit derived from a dianhydride, a first repeating unit, and a second repeating unit, or consists of a repeating unit derived from a dianhydride, a first repeating unit, and a second repeating unit.
[0039] 1.1. The first repeating unit
[0040] The first repeating unit is a repeating unit derived from an aliphatic diamine, which has a structure of the following formula (A), and the first repeating unit may include one or more repeating units having a structure of formula (A).
[0041] [Formula (A)]
[0042]
[0043] In formula (A), R 1 and R 2 Each is independent R 3 and R 4 Each is independent or H, wherein m and n are each independently an integer from 1 to 16, that is, each independently 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16, and * represents a bonding position, and The bonding position to carbon in the formula (A) is bonded to the aliphatic ring.
[0044] In a preferred embodiment of the present invention, the first repeating unit is a repeating unit having a structure of the following formula (A1), and the first repeating unit may include one or more repeating units having a structure of formula (A1).
[0045] [Formula (A1)]
[0046]
[0047] In formula (A1), m1, m2, n1, and n2 are each independently an integer from 0 to 14, that is, each independently 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14, and * represents a bonding position. Examples of repeating units having the structure of formula (A1) include, but are not limited to, the following repeating units: and Where * indicates the bonding position. In the following examples, the first repeating unit is
[0048] The first repeating unit is derived from a long carbon chain aliphatic diamine. Examples of the long carbon chain aliphatic diamine include, but are not limited to, dimer diamine. Herein, dimer diamine refers to a diamine having the following formula (A0).
[0049] [Formula (A0)]
[0050]
[0051] In formula (A0), m1, m2, n1, and n2 are each independently an integer from 0 to 14, that is, each independently 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14. Examples of diamines having the structure of formula (A0) include, but are not limited to
[0052] and Used in the following examples
[0053] In the polyimide of the present invention, the ratio of the first repeating unit is 1 mol% to 25 mol%, preferably 5 mol% to 20 mol%, such as 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, or 20 mol%, or within the range formed by any two of the above values. If the ratio of the first repeating unit is lower than the above range, the dielectric properties of the obtained polyimide may be poor. If the ratio of the first repeating unit is higher than the above range, the mechanical strength of the obtained polyimide may be poor, and the thermal expansion coefficient of the polyimide may be too high, resulting in deterioration of dimensional stability.
[0054] 1.2. Second repeating unit
[0055] The second repeating unit may be a repeating unit derived from an aromatic diamine, or a repeating unit having the following structure of formula (B), or a combination of the two, wherein * in formula (B) represents a bonding position, and the second repeating unit may include one or more repeating units derived from an aromatic diamine, and may also include one or more repeating units having the structure of formula (B). In one embodiment of the present invention, the second repeating unit is a repeating unit having the structure of formula (B). In another embodiment of the present invention, the second repeating unit includes a repeating unit derived from an aromatic diamine, or the second repeating unit is a repeating unit derived from an aromatic diamine.
[0056] [Formula (B)]
[0057]
[0058] The repeating unit derived from the aromatic diamine includes a structural unit represented by the following formula (C).
[0059] [Formula (C)]
[0060]
[0061] In formula (C), R 5 and R 6 Each is independent Covalent single bond, or where * indicates the bond position, and The bonding position to carbon in the formula (C) is bonded to the benzene ring of formula (C). In some embodiments of the present invention, the repeating unit derived from the aromatic diamine may include at least one structural unit selected from the following groups:
[0062] wherein * represents the bonding position. In a preferred embodiment of the present invention, the repeating unit derived from the aromatic diamine comprises Specifically, the repeating unit derived from the aromatic diamine may be or a combination thereof, wherein * indicates a bonding position.
[0063] Examples of aromatic diamines as a source of the repeating unit derived from an aromatic diamine include, but are not limited to, bis(4-aminophenyl)terephthalate (BPTP), 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ), 4-aminophenyl-4-aminobenzoate (APAB), bis(4-aminophenyl)decanoate (CPA), bis(4-aminophenyl)decanoate (D ... a-hydronaphthalene-2,6-dicarboxylate, ET-BDM), 2,7-bis(4-aminophenoxy)naphthalene (ET-2,7-Na), and N,N'-(4,4'-(9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(4-aminobenzamide), FDA-ADA. BPTP and ABHQ were used in the following examples.
[0064] The repeating unit having the structure of formula (B) may be a repeating unit derived from cyclohexanediamine. Examples of cyclohexanediamine include, but are not limited to, cis-1,2-cyclohexanediamine, trans-1,2-cyclohexanediamine, cis-1,3-cyclohexanediamine, trans-1,3-cyclohexanediamine, cis-1,4-cyclohexanediamine, and trans-1,4-cyclohexanediamine (t-CHDA). In the following examples, the repeating unit having the structure of formula (B) is derived from t-CHDA.
[0065] In some embodiments of the present invention, the ratio of the second repeating unit is 75 mol% to 99 mol%, preferably 80 mol% to 95 mol%, such as 80 mol%, 81 mol%, 82 mol%, 83 mol%, 84 mol%, 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, or 95 mol%, or within the range formed by any two of the above values. If the ratio of the second repeating unit is lower than the above range, the dielectric properties of the obtained polyimide may be poor. If the molar number of the second repeating unit is higher than the specified range, the thermal expansion coefficient of the obtained polyimide may be too low, resulting in the inability to match the thermal expansion coefficient of copper foil when applied to a flexible printed circuit board.
[0066] In some embodiments of the present invention, the molar ratio of the first repeating unit to the second repeating unit is 1:20 to 1:4, for example, 1:20, 1:19, 1:18, 1:17, 1:16, 1:15, 1:14, 1:13, 1:12, 1:11, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, or 1:4, or within a range consisting of any two of the above ratios. If the molar ratio of the first repeating unit to the second repeating unit is lower than the specified range, the obtained polyimide may not obtain better dielectric properties. If the molar ratio of the first repeating unit to the second repeating unit is higher than the specified range, the obtained polyimide may not obtain excellent mechanical strength and is not suitable as a material for preparing a flexible printed circuit board.
[0067] 1.3. Other repeating units derived from diamines
[0068] The polyimide of the present invention may optionally contain other repeating units derived from diamines, but to ensure the achievement of the purpose of the invention, the content of the other diamine repeating units is preferably 50 mol% or less based on the total molar number of all repeating units derived from diamines. For example, the other diamine repeating units may be repeating units derived from diamines containing ether groups (e.g., 4,4'-diaminodiphenyl ether) or repeating units derived from diamines containing ketone groups (e.g., 4,4'-diaminobenzophenone).
[0069] The other diamine repeating units include, but are not limited to, repeating units derived from one or more of 1,2-ethylenediamine, 1,2-propylenediamine, 1,3-diaminopropane, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(2-methylcyclohexylamine), and octamethylendiamine (OMDA), or repeating units derived from 4,4'-(hexafluoroisopropylidene)dianiline (6FPDA), 4,4'-(hexafluoroisopropylidene)bis(p-phenyleneoxy)dianiline (BAPHF), bis[4-(3-aminophenoxy)phenyl]sulfone (bis[4-(3-a The invention also provides a repeating unit of one or more of the following: 1,2-diaminophenoxy)phenyl]sulfone (BAPS), 4,4'-diaminobenzanilide (DABA), N1,N4-bis(4-aminophenyl)-terephthalamide (BPTPA), 4,4'-(4,4'-oxybis(4,1-phenylene)bis(oxy))bis(3-(trifluoromethyl)-aniline (p-6FAPE), and bis(4-aminophenyl)-cyclohexane-1,4-dicarboxylate (ES-C).
[0070] 1.4. Repeating units derived from dianhydrides
[0071] The polyimides of the present invention may comprise one or more repeating units derived from a dianhydride. The types of dianhydrides that can be used in the present invention are not particularly limited, and examples thereof include, but are not limited to, 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (PMDA), 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid-1,4-phenyl ester (TAHQ), 4,4'-bisphenol A dianhydride (BPADA), 4,4'-oxydiphthalic anhydride (BPADA), 4,4'-bisphenol A dianhydride (BPADA), 4,4'-bisphenol B dianhydride (BPAD), 4,4'-bisphenol A dianhydride (BPAD ... anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), and hydroquinonediphthalic anhydride (HQDA). a-BPDA, s-BPDA, BPADA, TAHQ, and PMDA were used in the examples that follow.
[0072] In some embodiments of the present invention, the repeating unit derived from the dianhydride may be selected from one or more of the following groups: and Where * indicates the bonding position.
[0073] As is well known to those skilled in the art, when analyzing the structure of the repeating units contained in the polyimide, the polyimide is usually subjected to an alkali treatment to distinguish the repeating units derived from the diamine and the repeating units derived from the dianhydride. After the alkali treatment, the repeating units derived from the dianhydride will first form acids, and then turn into acid anhydrides after high temperature treatment. and Repeating unit as an example, after alkali treatment, it will form and
[0074] 1.5. Preparation of polyimide
[0075] The preparation method of the polyimide of the present invention is not particularly limited. For example, the polyimide can be prepared by subjecting a dianhydride and a diamine to a condensation polymerization reaction to form a polyamic acid, and then heating and dehydrating the polyamic acid. Specifically, the diamine is first placed in a flask under a nitrogen atmosphere, and a solvent is added to completely dissolve the diamine, and then the dianhydride is added, and the intermediate solution is stirred at room temperature for 12 hours to obtain a polyamic acid solution, and then the polyamic acid is subjected to a dehydration ring-closing reaction at a high temperature to obtain the polyimide. Examples of solvents include, but are not limited to, N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (N,N-dimethylformamide), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile, hexamethylphosphorictriamide (HMPA), and 1,3-dimethyl-2-imidazolidinone (DMI). DMAc was used in the examples that follow.
[0076] 2. Polyimide film
[0077] The polyimide of the present invention can be used to form a film product. Therefore, the present invention also relates to a polyimide film. The formation method of the polyimide film of the present invention is not particularly limited. The polyimide can be coated with a coating method existing in the technical field of the present invention to form a film, or a polyamic acid solution can be coated with a coating method existing in the technical field of the present invention to form a polyamic acid film, and then the polyamic acid film is heated to close the polyamic acid loop to form a polyimide film. Examples of the existing coating methods include, but are not limited to, roller coating, blade coating, comma coating, mold coating, slit coating, wire rod coating, and spray coating.
[0078] In some embodiments of the present invention, the polyimide film of the present invention is prepared in the following manner. First, the polyamic acid solution is filtered to remove dust and impurities. Then, the polyamic acid solution is applied to a cleaned glass substrate with a scraper mold. Afterwards, the glass substrate coated with the polyamic acid solution is placed in a vacuum environment for 4 to 8 hours to slowly remove the solvent. Then, the glass substrate is placed in a high-temperature and vacuum oven to allow the polyamic acid to undergo a closed-loop reaction to form polyimide, thereby obtaining a polyimide film. Afterwards, the temperature is slowly lowered and then several stages of heat treatment are performed at a temperature of 100° C. to 500° C. to stabilize the properties of the polyimide film, and then the polyimide film is slowly cooled to room temperature.
[0079] The polyimide film of the present invention has excellent dielectric properties, excellent mechanical strength, excellent dimensional stability, lower water absorption and good heat resistance, and is particularly suitable as an insulating material for a flexible printed circuit board. The thickness of the polyimide film of the present invention is preferably 10 microns to 50 microns, such as 10 microns, 11 microns, 12 microns, 13 microns, 14 microns, 15 microns, 16 microns, 17 microns, 18 microns, 19 microns, 20 microns, 21 microns, 22 microns, 23 microns, 24 microns, 25 microns, 26 microns, 27 microns, 28 microns, 29 microns, 30 microns, 31 microns, 32 microns, 33 microns, 34 microns, 35 microns, 36 microns, 37 microns, 38 microns, 39 microns, 40 microns, 41 microns, 42 microns, 43 microns, 44 microns, 45 microns, 46 microns, 47 microns, 48 microns, 49 microns, or 50 microns, or within the range consisting of any two of the above numerical values.
[0080] 3. Example
[0081] 3.1. Measurement method
[0082] The present invention is further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:
[0083] [Thermal stability measurement]
[0084] The coefficient of thermal expansion (CTE) and glass transition temperature (Tg) of the polyimide film were measured using a thermomechanical analyzer (model: TMA Q400, purchased from TA Instruments). The measurement conditions are as follows: the polyimide film specimen used for measurement has a length of 10 mm, a width of 5 mm, and a thickness of 20 μm, the atmosphere is a dry nitrogen atmosphere, and the CTE test temperature range is 100° C. to 200° C. The unit of CTE is ppm / K.
[0085] [Mechanical property measurement]
[0086] The storage modulus (E') and loss modulus (E") of the polyimide film were measured as a function of temperature using a dynamic mechanical analyzer (DMA Q800, purchased from TA Instruments). The Young's modulus (E) of the polyimide film was calculated in GPa. The analysis conditions were as follows: the heating rate was 5°C / min, and the loading frequency (sine) was 1 Hz in air. The polyimide film specimen had a length of 20 mm, a width of 5 mm, and a thickness of 20 μm. After the Young's modulus (E) of at least four specimens was measured, the average value was calculated.
[0087] In addition, a universal testing machine (model: EZ Test Tensile Tester, purchased from Shimadzu) was used to perform a tension test on the polyimide film to obtain a stress-tension curve, and the ultimate tensile strength (UTS) and elongation at break (ε b The test conditions are as follows: the polyimide film test piece has a length of 15 mm, a width of 7 mm and a thickness of 20 μm, and the expansion rate is 2 mm / min. The ultimate tensile strength (UTS) and elongation at break (ε b ), calculate UTS and ε respectively b The unit of UTS is megapascal (MPa), ε b The unit is %.
[0088] [Dielectric property test]
[0089] A polyimide film test piece having a length of 8 cm, a width of 8 cm and a thickness of at least 10 μm was vacuum dried at 100°C for 24 hours, and then the dielectric constant (Dk) and the loss factor (Df) of the dried test piece were measured to obtain the dielectric properties before water absorption. The measurement was performed using a vector network analyzer (model: ZVB, purchased from Rohde & Schwarz) was performed at an analysis frequency of 10 gigahertz (GHz).
[0090] In addition, a polyimide film test piece having a length of 8 cm, a width of 8 cm and a thickness of at least 10 μm was immersed in water for 24 hours and then wiped dry, and the above-mentioned steps of measuring Dk and Df were performed to obtain the dielectric properties after water absorption.
[0091] [Water absorption test]
[0092] The water absorption of polyimide film is measured according to IPC-TM-650 2.6.2.1 and calculated by the following formula, where W 1 W represents the weight of the polyimide film after drying in an oven at 105°C for 1 hour. 2 It indicates the weight measured after the polyimide film was immersed in water at 23° C. for 24 hours and the water droplets on the film were wiped off. The test piece of the polyimide film has the dimensions of 2 inches in length, 2 inches in width and 25 μm in thickness.
[0093]
[0094] 3.2. Preparation of polyamic acid solution
[0095] [Example 1]
[0096] First, 0.83 g of ABHQ (purchased from Shifeng Company) and 0.07 g of C36 dimerdiamine (C36 DDA, model: Priamine 1074, purchased from Croda Company) were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and after 5.5 mmoles of glacial acetic acid were slowly dripped in, stirred for 10 minutes. Afterwards, 0.74 g of s-BPDA (purchased from UBE Company) was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmoles of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 1.
[0097] [Example 2]
[0098] First, 0.78 g of ABHQ and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 0.74 g of s-BPDA was added to the intermediate solution and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 2 was obtained.
[0099] [Example 3]
[0100] First, 0.70 g of ABHQ and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 0.74 g of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 3 was obtained.
[0101] [Example 4]
[0102] First, 0.83 g of BPTP (purchased from Shifeng Company) and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.74 g of s-BPDA was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 4.
[0103] [Example 5]
[0104] First, 0.27 g of t-CHDA (purchased from TCI) and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmoles of glacial acetic acid were slowly dripped in, and stirred for 10 minutes. Afterwards, 0.66 g of s-BPDA and 0.05 g of PMDA (purchased from TCI) were added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmoles of acetic anhydride were added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 5 was obtained.
[0105] [Example 6]
[0106] First, 0.26 g of t-CHDA and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.66 g of s-BPDA and 0.05 g of PMDA were added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 6 was obtained.
[0107] [Example 7]
[0108] First, 0.24 g of t-CHDA and 0.20 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.66 g of s-BPDA and 0.05 g of PMDA were added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 7 was obtained.
[0109] [Example 8]
[0110] First, 0.23 g of t-CHDA and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.66 g of s-BPDA and 0.05 g of PMDA were added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 8 was obtained.
[0111] [Example 9]
[0112] First, 0.83 g of BPTP and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 1.30 g of BPADA (purchased from TCI) was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 9 was obtained.
[0113] [Example 10]
[0114] First, 0.78 g of BPTP and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 1.30 g of BPADA was added to the intermediate solution and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 10.
[0115] [Example 11]
[0116] First, 0.07 g of BPTP and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. After that, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 11.
[0117] [Example 12]
[0118] First, 0.83 g of ABHQ and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.78 g of ODPA (purchased from TCI) was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 12.
[0119] [Example 13]
[0120] First, 0.78 g of ABHQ and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.78 g of ODPA was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 13 was obtained.
[0121] [Example 14]
[0122] First, 0.83 g of ABHQ and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 14.
[0123] [Example 15]
[0124] First, 0.78 g of ABHQ and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. After that, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 15.
[0125] [Example 16]
[0126] First, 0.70 g of ABHQ and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 16.
[0127] [Example 17]
[0128] First, 0.83 g of BPTP and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Afterwards, 1.15 g of TAHQ (purchased from Shifeng Company) was added to the intermediate solution and stirred at room temperature for 15 hours. Afterwards, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 17 was obtained.
[0129] [Example 18]
[0130] First, 0.78 g of BPTP and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 1.15 g of TAHQ was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 18 was obtained.
[0131] [Example 19]
[0132] First, 0.70 g of BPTP and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 1.15 g of TAHQ was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 19 was obtained.
[0133] [Example 20]
[0134] First, 0.83 g of ABHQ and 0.07 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 1.15 g of TAHQ was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Example 20 was obtained.
[0135] [Example 21]
[0136] First, 0.78 g of ABHQ and 0.13 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. After that, 1.15 g of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 21.
[0137] [Example 22]
[0138] First, 0.70 g of ABHQ and 0.27 g of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15 wt%. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. After that, 1.15 g of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Example 22.
[0139] [Comparative Example 1]
[0140] First, 0.87 g of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 0.74 g of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, thereby obtaining the polyamic acid solution of Comparative Example 1.
[0141] [Comparative Example 2]
[0142] First, 0.29 g of t-CHDA was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80 ° C, and a concentration of 10% by weight of the intermediate solution was prepared. Then, the intermediate solution was placed in an ice-water bath, and after 5.5 mmoles of glacial acetic acid were slowly dripped, stirred for 10 minutes. Afterwards, 0.66 g of s-BPDA and 0.07 g of a-BPDA (purchased from UBE) were added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmoles of acetic anhydride were added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 2 was obtained.
[0143] [Comparative Example 3]
[0144] First, 0.29 g of t-CHDA was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.70 g of s-BPDA and 0.03 g of PMDA were added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 3 was obtained.
[0145] [Comparative Example 4]
[0146] First, 0.87 g of BPTP was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. After that, 0.74 g of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 4.
[0147] [Comparative Example 5]
[0148] First, 0.29 g of t-CHDA was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 0.74 g of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 5.
[0149] [Comparative Example 6]
[0150] First, 0.29 g of t-CHDA was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 0.66 g of s-BPDA and 0.05 g of PMDA were added to the intermediate solution, and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 6 was obtained.
[0151] [Comparative Example 7]
[0152] First, 0.87 g of BPTP was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 7.
[0153] [Comparative Example 8]
[0154] First, 0.87 g of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Thereafter, 0.78 g of ODPA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 8.
[0155] [Comparative Example 9]
[0156] First, 0.87 g of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 1.30 g of BPADA was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain a polyamic acid solution of Comparative Example 9.
[0157] [Comparative Example 10]
[0158] First, 0.87 g of BPTP was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 1.15 g of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 10.
[0159] [Comparative Example 11]
[0160] First, 0.87 g of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, and the mixture was stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Next, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, followed by stirring for 10 minutes. Thereafter, 1.15 g of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. Thereafter, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, to obtain the polyamic acid solution of Comparative Example 11.
[0161] 3.3. Preparation of polyimide membrane
[0162] The polyamic acid solution of embodiments 1 to 22 and comparative examples 1 to 11 is used to prepare polyimide film. First, a filter head of 0.45 microns is used to filter the polyamic acid solution to remove dust and impurities. Then, the polyamic acid solution is applied to a cleaned glass substrate (length 20 cm, width 20 cm, thickness 0.5 cm) with a scraper mold. Afterwards, the glass substrate coated with the polyamic acid solution is placed in a vacuum environment for 6 hours to slowly remove the solvent. Then, the glass substrate coated with the polyamic acid solution is subjected to heat treatment for 1 hour at 100°C, 200°C, 300°C and 350°C in sequence, so that the polyamic acid is subjected to a thermal ring-closure reaction to form a polyimide film, and the properties of the polyimide film are stabilized. Finally, in order to avoid film rupture, the temperature is slowly cooled to room temperature before taking out to obtain the polyimide film of embodiments 1 to 22 and comparative examples 1 to 11.
[0163] The properties of the polyimide films of Examples 1 to 22 and Comparative Examples 1 to 11 were measured according to the measurement methods described above, including CTE, Tg, E, UTS, ε b , Dk, Df, and water absorption, and the results are recorded in Tables 1 to 8.
[0164] Table 1: Properties of polyimide films of Examples 1 to 3 and Comparative Examples 1 to 3
[0165]
[0166] Table 2: Properties of the polyimide films of Example 4 and Comparative Example 4
[0167]
[0168] Table 3: Properties of polyimide films of Examples 5 to 8 and Comparative Examples 5 to 6
[0169]
[0170]
[0171] Table 4: Properties of the polyimide films of Examples 9 to 11 and Comparative Example 7
[0172]
[0173] Table 5: Properties of the polyimide films of Examples 12 to 13 and Comparative Example 8
[0174]
[0175] Table 6: Properties of the polyimide films of Examples 14 to 16 and Comparative Example 9
[0176]
[0177]
[0178] Table 7: Properties of the polyimide films of Examples 17 to 19 and Comparative Example 10
[0179]
[0180] Table 8: Properties of the polyimide films of Examples 20 to 22 and Comparative Example 11
[0181]
[0182] As shown in Tables 1 to 8, the polyimide of the present invention has low dielectric properties (e.g., low Dk, low Df), low water absorption, high heat resistance (e.g., high Tg, low CTE), and high mechanical strength (e.g., high ε b , high UTS, high E). Specifically, Examples 1 to 3 show that when the polyimide comprises repeating units derived from a dianhydride and first repeating units derived from a long carbon chain aliphatic diamine and second repeating units derived from an aromatic diamine, the polyimide can simultaneously have low Df and water absorption, high ε b and Tg, and good CTE. Example 4 shows that when the polyimide comprises repeating units derived from a dianhydride, a first repeating unit derived from a long carbon chain aliphatic diamine, and a second repeating unit derived from an aromatic diamine, the polyimide can have high UTS and E. Examples 5 to 8 show that when the polyimide comprises repeating units derived from a dianhydride, a first repeating unit derived from a long carbon chain aliphatic diamine, and a second repeating unit derived from an aromatic diamine, even if two dianhydrides are used in combination, the polyimide can still have both low Dk and high ε. bExamples 9 to 22 show that when the polyimide comprises repeating units derived from a dianhydride and first repeating units derived from a long carbon chain aliphatic diamine and second repeating units derived from an aromatic diamine, even if different dianhydrides or different aromatic diamines are used, the polyimide can still have low Dk, low Df, high ε b , high Tg, high UTS, and low Dk and Df after water absorption.
[0183] In contrast, Comparative Examples 1 and 4 show that when the polyimide contains only the second repeating unit derived from the aromatic diamine and does not contain the first repeating unit derived from the long carbon chain aliphatic diamine, the Df of the polyimide is higher, ε b Comparative Examples 2 and 3 show that when the polyimide contains only the second repeating unit derived from the aromatic diamine and does not contain the first repeating unit derived from the long carbon chain aliphatic diamine, the Df and water absorption of the polyimide are unfavorably increased, ε b Comparative Examples 5 and 6 show that when the polyimide contains only the second repeating unit of the formula (B) but does not contain the first repeating unit derived from the long carbon chain aliphatic diamine, the Dk of the polyimide is high and ε b Comparative Examples 7 to 11 show that when the polyimide only comprises the second repeating unit having the structure of formula (B) but does not comprise the first repeating unit derived from the long carbon chain aliphatic diamine, even if the type of dianhydride or aromatic diamine is changed, the effect of the present invention cannot be provided.
[0184] The above embodiments are only used to illustrate the principle and efficacy of the present invention and to describe the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily completed by a person familiar with the present technology without violating the technical principle of the present invention are within the scope of the present invention.
Claims
1. A polyimide, characterized in that: comprising a repeating unit derived from a dianhydride and a first repeating unit and a second repeating unit derived from a diamine, The first repeating unit has a repeating unit of the following formula (A): [Formula (A)] In formula (A), R 1 and R 2 Each is independent R 3 and R 4 Each is independent or H, wherein m and n are each independently an integer from 1 to 16, * represents a bonding position, and The carbon-bonded position in the formula (A) is bonded to the aliphatic ring; and The second repeating unit is a repeating unit derived from an aromatic diamine, a repeating unit having the following structure (B), or a combination thereof: [Formula (B)] In formula (B), * represents a bonding position; and The repeating unit derived from an aromatic diamine comprises a structural unit having the following formula (C): [Formula (C)] In formula (C), R 5 and R 6 Each is independent Covalent single bond, or where * indicates the bond position, and The bonding position to carbon in the formula (C) is bonded to the benzene ring.
2. The polyimide according to claim 1, characterized in that The second repeating unit comprises the repeating unit derived from the aromatic diamine.
3. The polyimide according to claim 2, characterized in that The molar ratio of the first repeating unit to the second repeating unit is 1:20 to 1:
4.
4. The polyimide according to claim 1, characterized in that The second repeating unit has a repeating unit of formula (B), and a molar ratio of the first repeating unit to the second repeating unit is 1:20 to 1:
4.
5. The polyimide according to claim 1, characterized in that The repeating unit derived from an aromatic diamine comprises at least one structural unit selected from the following group: Where * indicates the bonding position.
6. The polyimide according to claim 5, characterized in that The repeating unit derived from an aromatic diamine is at least one selected from the following group: and Where * indicates the bonding position.
7. The polyimide according to any one of claims 1 to 6, characterized in that The first repeating unit has a repeating unit having the following structure: [Formula (A1)] In formula (A1), m1, m2, n1, and n2 are each independently an integer from 0 to 14, and * represents a bonding position.
8. The polyimide according to any one of claims 7, characterized in that The first repeating unit is at least one selected from the following group: and Where * indicates the bonding position.
9. The polyimide according to any one of claims 1 to 6, characterized in that The repeating unit derived from dianhydride is at least one selected from the following group: Where * indicates the bonding position.
10. The polyimide according to claim 9, characterized in that The repeating unit derived from the dianhydride is and combination.
11. A polyimide film, characterized in that: The polyimide is prepared from the polyimide according to any one of claims 1 to 10.